ELEANOR YOUNG’S OPPRESSION TOWARDS RACHEL CHU IN CRAZY RICH ASIANS (2018) - Ilfana, Della Elysia Aprilia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Crazy Rich Asians, directed by Jon M. Chu, tells the story of a couple, Rachel and Nick, who have very different social identities and social classes. This difference brought challenges that the couple had to face as many people disapproved of their relationship including Nick's mother, Eleanor Young. Deals with social identity and social class differences, which may cause oppression, this research seeks to uncover the types of oppression depicted in Crazy Rich Asians (2018) through Iris Young's oppression theory. This study identifies three specific forms of oppression in the film: cultural imperialism, powerlessness, and marginalization. It concludes that the portrayal of oppression in the film aligns with Iris Young's theory of the five faces of oppression. Keywords: Oppression, Cultural Imperialism, Powerlessness, Marginalization